1975
DOI: 10.1063/1.88139
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure of degraded heterojunction GaAlAs−GaAs lasers

Abstract: Transmission electron microscopy has been used to study the defects associated with the degradation of broad−contact geometry double−heterostructure lasers. Two different types of dislocation networks have been observed close to the active region of the degraded device having Burgers vectors of (a/2) 〈011〉 and a〈001〉. Both networks have been shown to be of interstitial character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…It is probably due to the transfer of interstitials from the type B defect networks to the type A ͗100͘ DLDs during annealing. 4 In other words, the observation of enlargement of ͗100͘ DLDs was related to the type A ͗100͘ DLDs. The type B defect networks could work as a sink for vacancies, thereby enhance the propagation of type A ͗100͘ DLDs.…”
Section: Total Force On Dislocation In In X Ga 1؊x As/gaas Structuresmentioning
confidence: 98%
See 2 more Smart Citations
“…It is probably due to the transfer of interstitials from the type B defect networks to the type A ͗100͘ DLDs during annealing. 4 In other words, the observation of enlargement of ͗100͘ DLDs was related to the type A ͗100͘ DLDs. The type B defect networks could work as a sink for vacancies, thereby enhance the propagation of type A ͗100͘ DLDs.…”
Section: Total Force On Dislocation In In X Ga 1؊x As/gaas Structuresmentioning
confidence: 98%
“…[4][5][6][7]9,12,13 TEM contrast techniques and stereo electron micrographs have also been used in the analysis of DLDs. These results showed that DLDs in different structures have similar nature which stretch along ͗100͘ and ͗110͘ directions ͑so-called ͗100͘ DLDs and ͗110͘ DLDs͒.…”
Section: Dark-line Defects (Dlds) In Gaas-based Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…6,30,31 Point defects, especially vacancies, have negligible diffusivities at room temperature. 32 However, the reaction probability increases if nonradiative recombination occurs in the vicinity of the defect, e.g., by a factor ϳ10 22 in Zn 0.67 Cd 0.33 Se.…”
Section: Bulk Diffusionmentioning
confidence: 99%
“…29 It is therefore surprising to find vacancy loops in such proportion in our case, although such loops have also been observed in conjunction with interstitial loops in degraded III-V devices. 30 The presence of degradation-induced defects involves the formation and/or diffusion of point or extended defects during bombardment. In the following we compare the models presented in previous studies with the help of the experimental situation depicted in Fig.…”
Section: Previous Models For the Degradation Mechanismmentioning
confidence: 99%